2021
DOI: 10.3332/ecancer.2021.1262
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the role of cyclin E1 overexpression as a predictive marker for the efficacy of bevacizumab in platinum-sensitive recurrent ovarian cancer

Abstract: The relative benefit of bevacizumab in ovarian cancer (OC) patients is greater the more the disease becomes platinum-resistant. Among other mechanisms of action, antiangiogenic agents may induce homologous recombination deficiency. Cyclin E1 (CCNE1) overexpression is a proposed marker of platinum resistance and is mutually exclusive with deficiency in homologous recombination. In this study, we evaluated the predictive value of CCNE1 expression with regard to the efficacy of bevacizumab. We retrospectively eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The protein expression of angiogenesis-related genes such as CCNE1, a disintegrin and metalloprotease 17 (ADAM17), mevalonate diphosphate decarboxylase (MVD), SMA_MVD, VEGFA, VEGFB, VGFR2, HIF-1α in tumor tissues was explored ( Fabbi et al, 2022 ). Only CCNE1 and VEGFB were proved to be predictive markers for the efficacy of bevacizumab ( Califano et al, 2021 ; Ribeiro et al, 2021 ). Circulating plasma or serum proteomic biomarkers are also assessed to their predictive value for PFS and OS.…”
Section: Biomarkers Of Anti-angiogenic Therapy In Ocmentioning
confidence: 99%
“…The protein expression of angiogenesis-related genes such as CCNE1, a disintegrin and metalloprotease 17 (ADAM17), mevalonate diphosphate decarboxylase (MVD), SMA_MVD, VEGFA, VEGFB, VGFR2, HIF-1α in tumor tissues was explored ( Fabbi et al, 2022 ). Only CCNE1 and VEGFB were proved to be predictive markers for the efficacy of bevacizumab ( Califano et al, 2021 ; Ribeiro et al, 2021 ). Circulating plasma or serum proteomic biomarkers are also assessed to their predictive value for PFS and OS.…”
Section: Biomarkers Of Anti-angiogenic Therapy In Ocmentioning
confidence: 99%
“…In particular, PFI >12 months, the only factor for the longterm duration of BMT and improved PFS, has been considered as an important prognostic factor in PSR because longer PFI may have a greater chance to show response to chemotherapy (16,17). Previous studies reported that overexpression of cyclin and reduced levels of anti-angiogenic proteins were related to longer PFI in recurrent ovarian cancer (18,19). Thus, notable survival benefit has been shown in patients with PFI >12 months, compared to those with PFI <6 months or 6-12 months (20).…”
Section: Discussionmentioning
confidence: 99%
“…Among other mechanisms of action, bevacizumab exposure may trigger HRD by inducing a hypoxic cellular state that can downregulate HR-related genes such as BRCA1/2 and RAD51 ( 117 ). In addition, the relative benefit of bevacizumab in EOC has been shown to increase as the disease becomes more platinum resistant ( 118 ). A retrospective analysis of 124 patients with platinum-sensitive recurrent ovarian cancer showed extended PFS with bevacizumab in patients with cyclin E1 overexpression (median 16.3 vs 7.1 months, P =0.010) ( 118 ).…”
Section: Treatment Options For Patients With Hrp Hgscmentioning
confidence: 99%
“…In addition, the relative benefit of bevacizumab in EOC has been shown to increase as the disease becomes more platinum resistant ( 118 ). A retrospective analysis of 124 patients with platinum-sensitive recurrent ovarian cancer showed extended PFS with bevacizumab in patients with cyclin E1 overexpression (median 16.3 vs 7.1 months, P =0.010) ( 118 ).…”
Section: Treatment Options For Patients With Hrp Hgscmentioning
confidence: 99%